Harnessing the power of blockchain technology to support decision-making in e-commerce processes - Al-Moghrabi, Khaldun G.; Al-Ghonmein, Ali M. (IAES International Journal of Artificial Intelligence (IJ-AI), 2024)
Technology, such as blockchain, has emerged as a promising solution for addressing the challenges of e-commerce decision-making. In this study, we explore the potential benefits of integrating blockchain technology into e-commerce and its role in supporting decision-making in e-commerce. We also examine blockchain’s benefits in terms of enhanced security, transparency, and efficiency for e-commerce platforms. Furthermore, the study discusses the challenges of implementing blockchain for e-commerce, including scalability, integration, regulatory frameworks, user experience, privacy, interoperability, and sustainability. By analyzing these challenges, the study provides valuable insights for future research and development efforts to facilitate a seamless adoption of blockchain technology in e-commerce decisions. Blockchain technology holds the potential to transform an e-commerce ecosystem by overcoming these challenges and unlocking its transformative potential.